Strategi Mitigasi Penyelenggaraan Ibadah Haji dan Umrah - Hanif Mu'azizah (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This policy paper describes that the long waiting time for the Hajj pilgrimage triggers people to choose to carry out the Umrah pilgrimage first through the Umrah Travel Organizer (PPIU) travel agency. The great interest of the Muslim community has caused the number of travel agencies to increase, thus causing competition in terms of financing and providing complete facilities to prospective pilgrims as part of the promotions offered. This creates a wide gap for rogue travel agents to commit fraud, so that quite a few people are trapped and suffer losses. Based on ultrasound analysis and tree diagrams, it was found that the current high public interest in the Hajj and Umrah pilgrimage is due to attractive travel agency offers, where the travel agency offers competitive prices, causing many prospective Hajj and Umrah pilgrims to become victims of fraudulent travel agency fraud in Indonesia. The policy recommendation that can be given is to issue a policy limiting regular Hajj registration for first-time pilgrims (First-Time Hajj Registration Policy) which is implemented with a one-time registration system in the national database of Hajj pilgrims as well as integrating Hajj data with Dukcapil, Immigration and SIPATUH to verify departure history.